How is preservice teachers’ gaze during classroom observation connected to their assessments of teaching quality? : A controlled study in screen-based and immersive video environments - Daltoè, Tosca; Appel, Tobias; Stark, Philipp; Brucker, Birgit; Dreher, Anika; Fauth, Benjamin; Friesen, Marita; Gerjets, Peter; Hansen, Linn; Trautwein, Ulrich; Göllner, Richard (Learning and Instruction, 2026)
Background: Teaching quality is commonly assessed through classroom observation. However, observer ratings of teaching quality frequently exhibit limited psychometric quality. Beyond evaluating the ratings themselves, exploring the observation process and the design of the video environment may offer valuable insights into conditions that enhance rating accuracy. Aims: This study explored the classroom observation process of preservice teachers using eye-tracking technology and examined how their gaze behavior relates to the accuracy of their teaching-quality ratings. We also investigated the impact of different video environments by comparing traditional classroom videos presented on computer screens with immersive 360-degree classroom videos presented on virtual-reality headsets. Sample: N = 75 preservice teachers participated in a controlled lab study. Method: Each participant observed two randomly assigned mathematics classroom videos—one in a traditional screen-based and one in an immersive video environment. Eye trackers recorded gaze behavior during critical classroom events. Participants rated the quality of the observed teaching after the video observations. Results: Overall, observers adjusted their gaze according to the focus of critical events (teacher- or student-focused). In immersive 360-degree videos, they showed a stronger visual focus on the teacher. Both visual focus of attention and cognitive arousal during critical events, indicated by a larger pupil diameter, predicted the accuracy of teaching-quality ratings, with gaze being a stronger predictor of rating accuracy in immersive compared to screen-based videos. Conclusions: The findings indicate that gaze behavior offers actionable insights into classroom observation processes and informs the design of observation environments in both research and teacher education.
Publisher Copyright: © 2025 The Authors
Keywords: Classroom observation; Classroom videos; Eye-tracking; Teaching quality